Refugees' Self-selection into Europe: Who Migrates Where? - Cevat Giray Aksoy; Panu Poutvaara (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
About 1.4 million refugees and irregular migrants arrived in Europe in 2015 and 2016. We model how refugees and irregular migrants are self-selected. Using unique datasets from the International Organization for Migration and Gallup World Polls, we provide the first large-scale evidence on reasons to emigrate, and the self-selection and sorting of refugees and irregular migrants for multiple origin and destination countries. Refugees and female irregular migrants are positively self-selected with respect to education, while male irregular migrants are not. We also analyze how border controls affect destination country choice.
Keywords: J15; J24; O15; 330; Refugees; self-selection; human capital; predicted income